Spatial Distribution and Genetic diversity of Tripneustes gratilla in Ambon Island - Silahooy, Veince Benyamin; Hakim, luchman; Toha, Hamid; ., widodo (Journal of Tropical Life Science, 2013)
Tripneustes gratilla an important ecological role in various habitats because T. gratilla is directly or indirectly recycling key from the nutrients in the waters of Ambon Island. Ambon Island has a distinctive topography, thus causing inhibition of water exchange period naturally in Ambon Bay and feared to complicate the exchange of genes between populations thus causing inbreeding. In addition the increasing environmental pollution can narrow the habitat of Tripneustes gratilla. Therefore, this study aims to determine the spatial distribution and genetic diversity of sea urchins (Tripneustes gratilla) on Ambon island based on cytochrome c oxidase subunit 1 gene. Alignment results showed the presence of genetic variation of T. gratilla on the Ambon island. This is shown in several polymorphic base where there has tranversi experience, transition, and insertion. COI gene sequence similarity values of T. gratilla on Ambon island is around 98.4 to 100%. Distribution of T. gratilla population found on Ambon island generally have a relatively small number of individuals. From four locations that just only one location have large enough number of individuals. However, the results of genetic analysis using COI gene showed the presence of genetic closeness between T. gratilla despite located in different locations.